Effect of external infusion connection devices replacement frequency on catheter related bloodstream infection - Wenchao Wang; Yuqing Wang; Yulu Xu; Weijie Shen; Guoping Lu; Ying Gu (Scientific Reports)
Abstract Timely and effective rescue of critically ill children no longer solely relies on advanced medical technology; vascular access plays a pivotal role. Best practice recommendations for nursing in vascular access are critical for ICU patients. However, clear guidelines for the maintenance of external infusion connection devices remain lacking. To address this gap, we conducted a prospective observational cohort study to examine the relationship between the number or replacement frequency of external infusion connection devices and catheter-related bloodstream infection (CRBSI). From September 2021 to December 2022, a total of 304 patients with a single non-tunneled central catheter were enrolled in our study. Our findings revealed no significant differences in CRBSI incidence based on the number or replacement frequency of external infusion connection devices during the catheter’s indwelling time (P > 0.05). Notably, coagulase-negative staphylococci, particularly Staphylococcus epidermidis, were the predominant pathogens in CRBSI cases.In real-world clinical settings, adherence to strict aseptic principles during infusion set use and replacement appeared to mitigate the correlation between device replacement frequency or number and CRBSI incidence.